Inhysningens betydelse för arbetsmiljön på svenska ridskolor : en jämförande studie av lösdriftsystem och traditionell hästhållning - Fransson, Therese; Söderman, Anna (SLU/Dept. of Anatomy, Physiology and Biochemistry (until 231231), 2018)
Today half a million Swedes are engaged in equestrian sports and the sport counts as Sweden's second largest youth sport. Equestrian practitioners consist of 90% women and they are also the ones who mostly perform the work in our riding schools. Working in a stable environment often implies high physical workload and exposure to risks. The horse sector is one of the least mechanized sectors that handle large animals and the work in the stables has barely developed in the last century. The purpose of this bachelor thesis is to investigate how loose housing work in comparison with traditional housing at riding schools regarding the work and safety of the staff with and around the horses. This bachelor thesis is part of a larger study - "Horse welfare, working environment, safety and pedagogics at Swedish riding schools". Our question formulations are: How do housing systems affect the stable workers regarding time, workload and safe working environment? Do there exist differences between traditional housing and loose housing systems? The data was collected at eight riding schools located in southern Sweden. Four of the riding schools apply a traditional horse housing system and four applied loose housing systems. Data was collected through video recording, checklists were used for record keeping and a questionnaire was made for the stable workers. Duration of the total time and the time for each moment was measured by the timekeeper on a cellphone and verified by the time on the video recording. Microsoft Office® Excel spreadsheet application was used to compile and analyze collected data. Literature for this thesis was searched in the Primo, Google Scholar, and Pub Med databases. Keywords: housing system, mechanization, ergonomics, workload, work environment, loose housing, horse keeping, health, risks, safety, riding instructors, musculoskeletal health, working conditions, physical workload, was used. The results for the evaluated discomfort at different working tasks showed that discomfort caused by physical workload occurred among eight workers at riding schools with traditional housing, compared to riding schools with loose housing where they only appeared on three of the workers. The time study shows noticeable differences in time spent on stable work, where the average working hours per horse in loose housing systems accounts for only 57% of the corresponding average value for working time per horse in the traditional housing systems. The work tas ”Mucking” proved to be the most demanding work regarding both physical workload and time spent. The self-perceived workload at riding schools with traditional housing showed that "mucking”, ”strew" and "coat horses" were estimated to be the most physically demanding work. At riding schools with loose housing "mucking" and "sweeping" were valued to be the most physically demanding work. Several of the studied work tasks did not occur at the riding schools with loose housing such as "sweep", "strew" and "coat horses". Conclusion of the study: The total time requirement is shortened and the workload decreases in riding schools with loose housing systems in comparison with riding schools with traditional housing. Mechanization of work shortens the overall work time and reduces the workload. A development regarding various housing systems and its mechanization in the horse sector can be achieved by raising awareness of the available opportunities to be used and by encouraging a critical self-thought and an open mind.